Analisis Desain dan Efektifitas Media Pembelajaran "Ulih Latih” untuk Meningkatkan Prestasi Belajar Siswa - Andre Sembiring; Nanang Khuzaini; Ririn Winarni (Journal on Education, 2024)
The purpose of this research is to determine the validity and effectiveness of the developed product. This research is an experimental type and a research and development (R&D) method using the ADDIE development model. The subjects used in this research include two material experts, two media experts, and students of class XI MIPA SMA Negeri 1 Sedayu. The control class is XI MIPA 3, and the experimental class is XI MIPA 4. The object of this research is the ULIH LATIH learning application. The instruments used consist of expert material validation questionnaires, expert media validation questionnaires, and pretest-posttest questions. The results of this research show that the ULIH LATIH learning application is "valid" both in terms of material and media for use in mathematics learning with an average score of 46 by material experts and 72.5 by media experts. The ULIH LATIH learning application has proven effective in improving student learning achievement, supported by statistical test results, including the Wilcoxon Signed Rank Test with a two-tailed p-value < 0.05, the Mann-Whitney U Test with a two-tailed p-value < 0.05, and a comparison of average scores showing an increase of 53.61 in the experimental class and 40.56 in the control class. This indicates that learning with the ULIH LATIH learning application is more effective in improving student learning achievement compared to learning without the ULIH LATIH learning application.